1980
DOI: 10.1182/blood.v56.5.835.835
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of bleeding in a patient with factor V inhibitor by platelet transfusions

Abstract: A 71-yr-old male was seen because of the development of severe bleeding diathesis secondary to an acquired factor V inhibitor. The lack of clinical and laboratory response to fresh frozen plasma prompted us to treat him with platelet transfusions during 4 separate bleeding episodes; on each occasion he received 1 0-1 5 U of homologous platelet concentrates. There was a remarkable clinical response associated with a marked correction of the prolonged prothrombin time. prolonged partial thromboplastin time. and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…It has been shown that in acquired FV deficiency due to the development of FV autoantibodies, platelet FV is relatively protected from antibody neutralization [65]. Platelet infusions have been reported to be effective in acquired FV deficiency [66] and may therefore also be an effective treatment alternative in patients with hereditary deficiency complicated by inhibitors. Prophylactic use of weekly platelet infusions was effective in one inhibitor patient in stabilizing a subdural haematoma [57].…”
Section: Factor V Inhibitorsmentioning
confidence: 99%
“…It has been shown that in acquired FV deficiency due to the development of FV autoantibodies, platelet FV is relatively protected from antibody neutralization [65]. Platelet infusions have been reported to be effective in acquired FV deficiency [66] and may therefore also be an effective treatment alternative in patients with hereditary deficiency complicated by inhibitors. Prophylactic use of weekly platelet infusions was effective in one inhibitor patient in stabilizing a subdural haematoma [57].…”
Section: Factor V Inhibitorsmentioning
confidence: 99%
“…Symptomatic FV inhibitors in F5D have been neutralized using large volumes of FFP (Di Paola et al, 2001) or intravenous immunoglobulin (Nesheim et al, 1986). Platelet transfusion was effective in acquired FV deficiency not related to F5D (Chediak et al, 1980). A specific FV concentrate (Kedrion Bipharma, Barga, Italy) is currently in clinical development.…”
Section: Managementmentioning
confidence: 99%
“…The patient reported here presented with mild bleeding symptoms, including purpuras and ecchymoses of the lower extremities. Patients with factor V inhibitors and active bleeding can be treated with fresh frozen plasma [1], platelet concentrates [12], prothrombin complex concentrate, activated prothrombin complex concentrate, plasmapheresis, or immunoadsorption [1]. For the elimination of factor V inhibitors, possible provoking medications should be discontinued.…”
Section: Discussionmentioning
confidence: 99%